Predicting soybean seed longevity under ambient storage through multivariate viability and vigor analysis - MOHAMED TAHA ZALAMA; AHMED A. A. LEILAH (Smujo International, 2025)
Abstract. Zalama MT, Leilah AAA. 2025. Predicting soybean seed longevity under ambient storage through multivariate viability and vigor analysis. Asian J Agric 9: 702-711. The current study examined the longevity of the soybean seed cultivar (Giza 111) under ambient storage conditions in Dakahlia, Egypt, from July 2023 to June 2024. Three lots of seed from different sources were observed for up to 360 days to predict seed longevity and to determine storage parameters for warehouse management. Initial seed quality was estimated, then a simplified viability equation, v = Ki - (1/?) P, was applied to predict seed longevity during the storage period. Significant differences were noticed among seed lots. Seed lot 01 (Legumes Department, FCRI, ARC) exhibited the best seed viability, with the highest storage index (? = 120 days), longest half-viability period (P50 = 151 days), and slowest deterioration rate (tg? = -0.0008), indicating superior vigor during storage. In contrast, seed lots 02 and 03, obtained from the private sector, showed reduced viability, with Lot 03 exhibiting the lowest (? = 90 days, tg? = -0.011, P50 = 79 days). Linear regression showed seed viability decline rates differed: Lot 01 (slowest, -2.50), Lot 02 (moderate, -2.73), and Lot 03 (fastest, -3.34), confirming relative deterioration speeds. Pearson correlation analysis showed a strong positive correlation between probit viability and seed vigor indices, including germination (r = 0.946), accelerated aging (r = 0.945), seedling dry weight (r = 0.925), and vigor index II (r = 0.935). Quantitative data further supported the correlation between probit viability and vigor parameters. This study demonstrated that a simplified viability equation effectively predicted the longevity and vigor of soybean seeds from different sources stored under ambient conditions in Dakahlia, Egypt. Significant differences in viability and deterioration rates among seed lots underscore the equation's value for practical seed storage monitoring, improved ambient storage management, and enhanced seed inventory control and quality preservation through accurate performance prediction.